Vision: The Case for Cellular Small Cells for Cloudlets - Agarwal, Sharad; Philipose, Matthai; Bahl, Victor (International Workshop on Mobile Cloud Computing & Services, 2014)
Today’s cellular networks are built with“macro cell” basestations connected to the Internet via a rigid, complicated backhaul. Even with state-of-art technologies like LTE, users get limited throughput and high latency, with high variance. Performance enhancing IP boxes are deployed in the cellular operator’s datacenters, far from the user. As a result, the most compelling cloudlet applications are difficult to realize on such networks and cloudlet researchers have thus far focused on Wi-Fi networks only. We argue that the cloudlet community should consider small cell networks in addition to Wi-Fi networks. Small cells, such as femtocells and picocells, are relatively new additions to the cellular standards. By reducing the cell size compared to the traditional macro cells, they increase spatial reuse of precious licensed frequencies. Users get higher bandwidth and lower latency, with relatively less variance. This architecture, where small cells are deployed simply with power and Ethernet connectivity, lends itself well to cloudlet augmentation. In this position paper, we describe why deployed macro cell basestations are unsuitable for cloudlet deployment. In contrast, we describe why a small cell architecture is amenable for cloudlet deployments. Our experience from operating a small cell testbed in licensed frequencies matches that reported by equipment vendors. The applications we care about require high throughput and low latency. In a cellular network this can be achieved today by augmenting small cells with powerful cloudlets.